Perception of mathematics teachers on school-based assessment using Q-methodology approach - Lim, Ching Yee (2014)
This study explored the views of Malaysian lower secondary school mathematics teachers who were the implementers of a new assessment reform, School-Based Assessment (SBA). Teachers are crucial implementers and main change agents for any new innovation. Therefore, teachers perceptions may have an impact on underpinning the success or failure of the educational reforms. Furthermore, many studies related to SBA have been conducted on other subjects but none was found pertaining to mathematics teachers. Therefore, there is a research gap pertaining to mathematics teachers’ perceptions on SBA. Fullan’s Educational Change Model were adopted and provided as the theoretical base for this study. Q-methodology was employed due to its appropriateness and relevant means of exploring human subjectivity such as perception.The procedures of the methodology include collecting concourse, developing Q-sample, identifying P-set, conducting Q-sort as well as analysing data. There were 72 Form One and Form Two mathematics teachers who were volunteered to participate in this study. Each participant was required to rank 44 statements about the implementation of SBA according to how closely the statements align with their personal beliefs, experience and perceptions. Factor analysis was performed to identify the commonalities and patterns in their perceptions. Three significant factors were revealed from PQMethod analyses, namely: Relevance and Complexity, Readiness and Resources, Readiness and Complexity. Three factors extracted represented the different perceptions of three groups of mathematics teachers. Firstly, 57% of teachers did not acknowledge the benefits and advantages that SBA can bring to them and their students, teachers also found it was complex. The second emerging factor was Readiness and Resources, whereby, 18% of the teachers were ready and committed towards SBA, however, lack of resources had demoralised their spirit. The third factor, Readiness and Complexity, whereby, 25% of teachers perceived lack in readiness and preparation thus found that SBA was complex to handle in their classes. The findings drawn from this study might provide some insights to Malaysian government to explore more practical options to implement better assessment. Malaysian teachers are more willing to accept the changes when they discovered that there are positive changes which can benefit them and their students.